2020
DOI: 10.3390/fermentation6030080
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Wine Saccharomyces cerevisiae Strains and Their Screening for the Adsorption Activity of Pigments, Phenolics and Ochratoxin A

Abstract: Ochratoxin A is a dangerous mycotoxin present in wines and is considered the principal safety hazard in the winemaking process. Several authors have investigated the ochratoxin A adsorption ability of Saccharomyces cerevisiae yeasts, and specifically selected strains for this desired trait. In the present work, a huge selection of wine yeasts was done starting from Portuguese, Spanish and Italian fermenting musts of different cultivars. Firstly, 150 isolates were collected, and 99 non-redundant S. cerevisiae s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
(59 reference statements)
2
11
0
Order By: Relevance
“…Our results were consistent with these reports, with all selected being within the optimal range with the exception of H. uvarum 26/17, the highest producer as reported for the species by Aponte and Blaiotta [99]. However, the behavior of this strain confirmed the utility of the visible halo as a screening test [16,77,100].…”
Section: Discussionsupporting
confidence: 92%
“…Our results were consistent with these reports, with all selected being within the optimal range with the exception of H. uvarum 26/17, the highest producer as reported for the species by Aponte and Blaiotta [99]. However, the behavior of this strain confirmed the utility of the visible halo as a screening test [16,77,100].…”
Section: Discussionsupporting
confidence: 92%
“…Results from our study (Figure 3) indicated that the highest value for color intensity of Vranec wines V1 and V3 fermented by yeast strains F-8 and D-80, respectively, as well as the Cabernet Sauvignon wine CS3 fermented by yeast strain D-80. Such a behavior led us to show that isolated autochthonous yeast strains do not always meet all the desired phenotype traits for winemaking but, important to mention, they contribute effectively to the biodiversity and microbial heritage, which can be very useful to develop and improve new and successful fermentation processes toward the innovation, diversity, and authenticity of wines [43][44][45][46]. The existence of yeast strains with superior genetic traits and technological potential can be achieved through the exploitation of the variety of grape and optimization of the fermentation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…, Rhodotorula glutinis Different wine-grapes of Turkey Phosphate-buffered saline (PBS) and white wine 25 °C, 4 h 8 1 1.96–26.11/4.1–31.31 viable/dead Var et al (2009) Candida intermedia a Grape juice 25 °C, 48 h, 100 rpm, in the dark 9 20 >80 immobilized yeast cells Farbo et al (2016) Debaryomyces hansenii a YMB medium 28 °C, 24 h, shaking (300 rpm) 5.3 7 >98 viable/dead Gil-Serna et al (2011) Phaffia rhodozyma PM broth (0.5% yeast extract, 1% sucrose, 0.5% peptone and 0.2% malt extract) 20 °C, 15 d 6 7.5 23/45 viable/dead Zhao et al (2020) Saccharomyces cerevisiae a Red, rose and white must samples 12 °C, 90 d 0.01, 0.5, 1.0, 2.0 and 4.0 73–90 viable Csutorás et al (2013) . Saccharomyces cerevisiae a Wine 28 °C, 10 d 0.005 34.52–48.96 viable Pulvirenti et al (2020) Kefir grains (Lactobacillus kefiri , Kazachstania servazzii , Acetobacter syzygii) a Milk Aerobically, 25 °C, 24 h 7–11 1 15–81 viable Taheur et al (2017) . Saccharomyces cerevisiae Grapes Grapes must 25 °C 6 2000 6.42–8.59 …”
Section: Control Of Ota Contamination By Biological Approachesmentioning
confidence: 99%